Moment of battle the twenty clashes that changed the world - Lacey, James (Bantam Books, 2013)
Two modern masters of military history make the case for the twenty most pivotal battles of all time, in a riveting trip through the ages to those moments when the fate of the world hung in the balance. Includes Marathon, Gaugamela, Zama, Teutoburger Wald, Adrianople, Yarmuk, Hastings, The Spanish Armada, Breitenfeld, Annus mirabilis, Saratoga, Trafalgar, Vicksburg, The Marne, The Battle of Britain, Midway, Kursk, Normandy, Dien Bien Phu, and Operations peach.